Optical Solutions of Schrödinger Equation Using Extended Sinh–Gordon Equation Expansion Method - Irshad, Amna; Ahmed, Naveed; Khan, Umar; Mohyud-Din, Syed Tauseef; Khan, Ilyas; Sherif, El-Sayed M. (Frontiers in Physics, 2020)
In this paper, we investigated nonlinear Schrödinger equation(NLS) to extract optical soliton solutions by implementing Extended Sinh-Gordon equation expansion method(ShGEEM). Optical soliton solutions included bright, dark, combined bright-dark, singular soliton combined singular soliton solutions, singular periodic wave solutions. Comparison of our new results have been presented to results exist in literature. Also, graphical analysis presented with 3D and contour graphs to understand the physics of obtained solutions.